IMPACT OF HYGIENE BATHING AND BREASTFEEDING OF LACTATING MOTHERS ON INFANT MORTALITY IN KATSINA STATE - SANI BALA; ANIFAT ABDURRAHEEM (International Studies Journal)
The study examines the influence of cultural practices in terms of attitudes that feeding mothers exhibit towards infant breastfeeding, and infant bathing (general hygiene) on infant mortality in Katsina State. It makes use of a descriptive research design which makes it possible for the collection of data from the selected samples (384) of the population that constitute women of bearing age, medical doctors, nurses and traditional birth attendants.  The needed data to address the research questions was collected by making use of copies of questionnaire and structured interview.  A multi-samplinig technique was applied in selecting the samples for the study, and the findings indicate that there is a significant positive correlation between hygiene bathing and the attitude of lactating mothers towards breastfeeding their children especially at early hours of delivery on one hand, and level of infant mortality in the study area.  It is, therefore, recommended among others that campaigns for infant breastfeeding awareness need to be intensified. This will educate women to understand the dangers associated with delay, denial, and importance offrequent breast feeding of infant at regular interval.